Anti-icing and de-icing graphene workpiece with electric heating performance and preparation method of anti-icing and de-icing graphene workpiece

By forming and processing graphite modules on the surface of the diamond matrix, a high-angle graphene layer is formed, and the electric heating performance is improved through parallel electric heating circuits, the problem of insufficient performance of electric heating elements in the existing electric heating deicing system is solved, and an efficient and durable electric heating anti-icing effect is achieved.

CN119893768AActive Publication Date: 2025-04-25NANJING UNIV OF AERONAUTICS & ASTRONAUTICS
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510251179.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-04
Publication Date
2025-04-25
Estimated Expiration
2045-03-04

AI Technical Summary

Technical Problem

In the existing electrical heating and deicing systems, the metal resistive wire has poor wear resistance, torsion resistance and corrosion resistance, and the electric heat conversion efficiency is not high, resulting in electrical energy loss. At the same time, the graphene preparation process consumes high energy, may introduce impurities, affect performance, and the interaction between graphene and the substrate is weak, limiting the durability of the film.

Method used

The graphite module is formed by laser irradiation on the surface of the diamond matrix, and through mechanical cleavage and electrochemical peeling treatment, the angle between the graphene sheet of the graphene layer and the surface of the diamond matrix is ​​80-90°, forming a graphene layer with a micro-nano scale nearly vertical, and finally undergoing hydrophobic treatment to form an ice-proof graphene product with electric heating properties, and further improving the electric heating performance through parallel electric heating circuits.

Benefits of technology

It improves the electric heating performance and durability of graphene parts, enhances the interface bonding force with the substrate, improves the electric heating conversion efficiency and the highest steady-state temperature, and has a super-hydrophobic structure, suitable for aircraft electrical thermal anti-icing applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005296991490000081
    Figure BDA0005296991490000081
  • Figure BDA0005296991490000082
    Figure BDA0005296991490000082
  • Figure HDA0005296991500000011
    Figure HDA0005296991500000011
Patent Text Reader

Abstract

The invention provides an anti-icing and de-icing graphene workpiece with electric heating performance and a preparation method, and the method comprises the following steps: carrying out laser irradiation treatment on the surface of a diamond substrate, and forming a plurality of parallel graphite modules on the surface of the diamond substrate; the outer layers of the graphite modules are subjected to mechanical cleavage treatment, so that the outer layer of each graphite module is cleaved into a graphene layer, and the angle between a graphene sheet in each graphene layer and the surface of the diamond substrate is 30-40 degrees; the graphene layer is subjected to electrochemical stripping, so that the angle between a graphene sheet in the graphene layer and the surface of the diamond substrate is 80-90 degrees, and a micro-nano-scale nearly-vertical graphene layer is formed; and finally, hydrophobic treatment is conducted, and the anti-icing and deicing graphene workpiece with the electric heating performance is obtained. Through the parallel electric heating loop composed of the vertical graphene modules, the electric heating performance of the assembly can be effectively improved, heating is more uniform, the highest steady-state temperature is higher, the electric heating conversion efficiency is higher, meanwhile, the hydrophobic function is achieved, and the requirement for electric heating ice prevention and removal of an airplane can be better met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of electrothermal graphene preparation, and in particular relates to an anti-icing graphene component with electrothermal performance and a preparation method thereof. Background Art

[0002] The most widely used and mature system on aircraft at present is the electric heating de-icing system. Traditional electric heating de-icing systems usually use metal resistance wire as the electric heating element of the de-icing system. However, metal resistance wire still has obvious disadvantages, mainly manifested in poor wear resistance, bending resistance and corrosion resistance. In addition, it may produce inductive effect under external voltage, and the electric heat conversion efficiency is not high, resulting in power loss.

[0003] Graphene is a single-atom-layer two-dimensional carbon nanomaterial. Carbon atoms are connected based on sp2 hybridization. It is the thinnest and strongest material currently available. It also has a huge specific surface area and excellent thermal properties. The thermal conductivity is between 4840 and 5300 W / (m·K), which is the carbon material with the highest thermal conductivity. However, most graphene preparations use graphene oxide as the raw material. In order to reduce graphene oxide to graphene with high electrical conductivity and high thermal conductivity, chemical, electrochemical or thermal reduction methods are usually required. These processes are not only energy-intensive, but may also introduce impurities or defects, affecting the performance of graphene. Secondly, when graphene is coated on an insulating substrate to prepare a film, the interaction between graphene and the substrate is often weak, which limits the durability and application range of the film. Weak bonding may cause graphene to fall off or crack easily during use, especially when it undergoes changes in external conditions such as temperature changes, mechanical stress or chemical erosion. Enhancing the interfacial bonding between graphene and the substrate and improving the stability and service life of the film are also important considerations. In addition, the thermal conductivity between graphene and silicon or metal interfaces is limited, mainly due to the increase in thermal resistance at the interface, which limits the application potential of graphene in high-performance electronic devices, thermal management materials and other fields.

[0004] Based on the above, the present invention provides an anti-icing graphene component with electrothermal performance and a preparation method, which not only has the excellent electrothermal performance of graphene, but also can further improve its electrothermal performance through a parallel circuit. Summary of the invention

[0005] The purpose of the present invention is to address the deficiencies in the prior art and provide an anti-icing graphene component with electrothermal properties and a preparation method, which can generate vertical graphene with excellent electrothermal properties on the surface of a flat diamond-coated component and form a parallel electrothermal circuit, thereby effectively improving the electrothermal anti-icing effect of the component.

[0006] In order to achieve the above technical objectives, the present invention adopts the following technical solutions:

[0007] (I) The present invention provides a method for preparing an anti-icing graphene component with electrothermal performance, comprising the following steps: subjecting the surface of a diamond substrate to laser irradiation treatment to form a plurality of mutually independent graphite modules on the surface of the diamond substrate; subjecting the outer layer of the graphite module to mechanical cleavage treatment to cleave the outer layer of each graphite module into a graphene layer formed by a plurality of graphene sheets, wherein the angle between the graphene sheets in the graphene layer and the surface of the diamond substrate is 30 to 40°; subjecting the graphene layer to electrochemical exfoliation to the angle between the graphene sheets in the graphene layer and the surface of the diamond substrate is 80 to 90°, thereby forming a micro-nano scale nearly vertical graphene layer; subjecting the surface of the micro-nano scale nearly vertical graphene layer to hydrophobic treatment to obtain an anti-icing graphene component with electrothermal performance.

[0008] Furthermore, the diamond substrate is a diamond-coated component, including a substrate and a diamond coating, wherein the diamond coating is prepared on the substrate by a chemical vapor deposition method, and the thickness of the diamond coating is not greater than 20 μm.

[0009] Furthermore, the plurality of graphite modules are parallel to each other and equidistantly distributed, one end of the plurality of graphite modules is bonded to the first copper foil sheet through conductive silver paste, and the other end of the plurality of graphite modules is bonded to the second copper foil sheet through conductive silver paste. The first copper foil sheet and the second copper foil sheet are respectively connected to the positive electrode and the negative electrode of the power supply to form a parallel electric heating circuit with a certain resistance value. The first copper foil sheet and the second copper foil sheet are spaced 10 mm apart.

[0010] Furthermore, among the plurality of graphite modules, the distance between two adjacent graphite modules is 0.8-1 mm, and the width of the graphite module is 1 mm; and the thickness of the micro-nano-scale nearly vertical graphene layer is 12 μm.

[0011] Furthermore, the hydrophobic treatment is specifically as follows: immersing the micro-nano scale nearly vertical graphene layer in a fluorinated liquid for 18 to 20 minutes, preferably 20 minutes, to obtain an anti-icing graphene product.

[0012] Furthermore, the equipment used for the laser irradiation treatment is a nanosecond laser; in the laser irradiation operation, the pulse frequency is 30kHz, the spot diameter is 20μm, the laser power is 8W, and the scanning interval is 1μm; the angle between the nanosecond laser incident direction and the surface of the diamond substrate is 80°.

[0013] Furthermore, the equipment used for the mechanical cleavage includes a flywheel with an outer diameter of 120 mm and a thickness of 8 mm. During the mechanical cleavage process, the flywheel feed control accuracy is 1 μm and the flywheel rotation speed is 2000 r / min.

[0014] Furthermore, the electrochemical stripping operation is specifically as follows: using a graphene product with an angle of 30 to 40° with the surface of the diamond substrate as a working anode and a platinum sheet as a working cathode for electrochemical stripping, applying a voltage of 10 V during stripping, and a stripping time of 30 minutes.

[0015] Furthermore, in the electrochemical stripping operation, the electrolyte is a mixed aqueous solution of (NH4)2SO4 and NaOH, and the pH of the electrolyte is 9.

[0016] Furthermore, the size of the platinum sheet is 10×15×0.1 mm 3 , purity>99.9%; the positive and negative poles are placed in parallel with a distance of 3cm.

[0017] (ii) The present invention also provides an anti-icing graphene component with electrothermal performance, which is prepared by the method described above, wherein the graphene component comprises a diamond substrate and a plurality of mutually parallel graphite modules, the surfaces of the graphite modules are sequentially connected to a graphene layer and a hydrophobic layer; the angle between the graphene sheets of the graphene layer and the surface of the diamond substrate is 80 to 90°; the diamond substrate, the graphite modules and the graphene layers are sequentially connected by carbon-carbon covalent bonds.

[0018] Compared with the prior art, the present invention has the following beneficial effects:

[0019] (1) The present invention forms a plurality of parallel graphite modules on the surface of a diamond substrate by laser irradiation treatment, and mechanically cleaves each graphite module to obtain a graphene layer, wherein the angle between the graphene sheet in the graphene layer and the surface of the diamond substrate is 30 to 40°, and finally, electrochemical stripping is performed to change the angle between the graphene sheet in the graphene layer and the surface of the diamond substrate from 30 to 40° to 80 to 90°, thereby obtaining a more excellent electrothermal performance, and finally, the anti-icing effect is achieved by hydrophobic treatment;

[0020] (2) The present invention provides a parallel electric heating circuit composed of evenly distributed vertical graphene modules, which can more effectively improve the electric heating performance of the component. The graphene component is heated more evenly, has a higher maximum steady-state temperature, and has a higher electric heat conversion efficiency.

[0021] (3) Compared with conventional graphene with electrothermal properties, the method provided by the present invention can directly generate electrothermal graphene in situ on the diamond surface, which is simpler to operate and saves production and application costs;

[0022] (4) The method provided by the present invention not only solves the problem of uneven heating of existing electric heating parts, but also improves the maximum steady-state temperature and electric heat conversion efficiency. At the same time, it has a super-hydrophobic structure, which can better meet the needs of electric heating anti-icing of aircraft. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 A schematic diagram of an anti-icing graphene product with electrothermal performance prepared in Example 1;

[0024] Figure 2 This is a surface SEM image of the anti-icing graphene product with electrothermal performance prepared in Example 1;

[0025] Figure 3 This is a scanning electron microscope image of the workpiece in Example 1 after mechanical cleavage and chemical stripping treatment, wherein: Figure 3 a is an electron microscope image of the graphene layer after mechanical cleavage treatment in step 2 of Example 1, Figure 3 b is an electron microscope image of the graphene layer after electrochemical stripping in step 3 of Example 1;

[0026] Figure 4 The surface water contact angle of the anti-icing graphene article with electrothermal performance prepared in Example 1;

[0027] Figure 5 The temperature rise curves of the anti-icing graphene component with electrothermal performance and the metal wire electrothermal film prepared in Example 1 under the same heat flux density. DETAILED DESCRIPTION

[0028] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0029] The present invention provides an anti-icing graphene component with electrothermal performance, wherein the graphene component comprises a diamond substrate and a plurality of graphite modules which are parallel to each other and equidistantly distributed, wherein a graphene layer and a hydrophobic layer are distributed on the upper layer of each graphite module, wherein the angle between the graphene sheet of the graphene layer and the surface of the diamond substrate is 80-90°, and the diamond substrate, the graphite module and the graphene layer are sequentially connected by carbon-carbon covalent bonds.

[0030] The preparation method comprises the following steps:

[0031] First, the surface of the diamond substrate is subjected to structured laser irradiation treatment to form a number of independent graphite modules on the surface of the diamond substrate to obtain a graphite layer-containing component. Second, the outer layer of the graphite module is subjected to mechanical cleavage treatment to cleave the outer layer of each graphite module into a graphene layer formed by multiple graphene sheets, and the angle between the graphene sheets in the graphene layer and the surface of the diamond substrate is 30 to 40°. Third, the graphene layer is subjected to electrochemical exfoliation to make the angle between the graphene sheets in the graphene layer and the surface of the diamond substrate 80 to 90°, forming a micro-nano-scale nearly vertical graphene layer. Fourth, the surface of the micro-nano-scale nearly vertical graphene layer is subjected to hydrophobic treatment to obtain an anti-icing graphene component with electrothermal properties.

[0032] The present invention has no special restrictions on the type of diamond matrix, and it can be either natural diamond or artificial diamond, preferably artificial diamond, and more preferably CVD diamond. In the present invention, the diamond is preferably a diamond sheet, and the present invention has no special restrictions on the size of the diamond sheet. In a preferred embodiment of the present invention, the size of the diamond sheet is specifically 10mm×10mm×0.4mm (length×width×thickness);

[0033] In the present invention, the plurality of graphite modules are parallel to each other and equidistantly distributed, one end of the plurality of graphite modules is bonded to the first copper foil metal sheet through conductive silver paste, and the other end of the plurality of graphite modules is bonded to the second copper foil metal sheet through conductive silver paste. The first copper foil metal sheet and the second copper foil metal sheet are connected to the positive electrode of the power supply and the negative electrode of the power supply, respectively, to form a parallel electric heating circuit. The present invention does not limit the spacing between the first copper foil metal sheet and the second copper foil metal sheet. In an embodiment of the present invention, the spacing between the first copper foil metal sheet and the second copper foil metal sheet is 10 mm.

[0034] In addition, the present invention does not limit the distance between graphite modules and the size of a single graphite module. In an embodiment of the present invention, the distance between two adjacent graphite modules is 0.8 to 1 mm, and the size of the graphite module is 10 mm (length) × 1 mm (width), so that the parallel circuit composed of vertical graphene modules has the highest electrothermal conversion efficiency.

[0035] For laser irradiation operation: the equipment used for laser irradiation treatment is a nanosecond laser, and the preferred operating parameters of the embodiment of the present invention are: the pulse frequency is 30kHz, the spot diameter is 20μm, the laser power is 8W, the scanning interval is 1μm, and the laser irradiation is carried out in an air atmosphere. Through laser irradiation treatment, the diamond on the surface of the diamond substrate will phase change into graphite to form a graphite layer of a certain thickness. With the help of the precision of the laser, the present invention can ensure the accuracy of the electrothermal graphene generation area, and can generate electrothermal graphene in a fixed shape and positioning. In addition, based on the consideration of heat dissipation of the diamond substrate during laser irradiation treatment, the angle between the laser incident direction of the pulsed laser and the surface to be processed of the diamond substrate is 80 to 85°.

[0036] For the mechanical cleavage operation: after obtaining the graphite layer-containing workpiece, the graphite layer-containing workpiece is mechanically cleaved, so that the outer layer of the graphite layer is cleaved into a graphene layer formed by multiple graphene sheets, and the angle between the graphene sheets in the graphene layer and the surface of the diamond substrate is 30-40°. The equipment used for mechanical cleavage includes a flywheel made of stainless steel, with an outer diameter of 120 mm and a thickness of 8 mm; the operating conditions of the mechanical cleavage include: the flywheel feed control accuracy is 1 μm, and the flywheel speed is 2000 r / min.

[0037] For the electrochemical stripping operation: after obtaining the graphene layer product, the present invention performs electrochemical stripping on the graphene layer product. The preferred electrochemical stripping operation process in the embodiment of the present invention is: using the graphene product with an angle of 30 to 40° with the surface of the diamond substrate as the working anode, and using a platinum sheet (purity> 99.9%) as the working cathode for electrochemical stripping, the positive and negative electrodes are placed in parallel, the electrolyte is a mixed solution of (NH4)2SO4 and NaOH, preferably with a pH value of 9, the applied voltage during stripping is 10V, and the stripping time is 30min.

[0038] The hydrophobic treatment operation is specifically as follows: immersing the micro-nano scale nearly vertical graphene layer in a fluorinated liquid for 18 to 20 minutes, preferably 20 minutes, to obtain an anti-icing graphene product. In other embodiments of the present invention, other hydrophobic treatment materials can also be selected for hydrophobic operation, and those skilled in the art can select them according to their needs, and the present invention does not limit them.

[0039] Compared with the traditional graphene with electrothermal performance, the present invention generates a nearly vertical graphene layer of Wiener scale in situ on the diamond surface, and the graphene is evenly distributed on the diamond surface. The graphene sheets overlap each other to form a good conductive grid, thereby obtaining excellent electrothermal performance. In addition, the present invention bonds the two ends of several equidistantly distributed and parallel graphite modules to copper foil metal sheets through conductive silver paste, and the copper foil metal sheets at both ends are respectively connected to the positive pole of the power supply and the negative pole of the power supply to form a parallel electrothermal circuit, which can further improve the electrothermal performance of the product. The method provided by the present invention not only solves the problem of uneven heating of existing electrothermal products, but also improves the maximum steady-state temperature and electrothermal conversion efficiency, and at the same time has a super-hydrophobic structure, which can better meet the needs of aircraft electrothermal anti-icing.

[0040] Example 1

[0041] The embodiment of the present invention provides an anti-icing graphene component with electrothermal performance, and the preparation method thereof comprises the following steps:

[0042] Step 1: Laser irradiation treatment:

[0043] A CVD diamond sheet with a size of 10 mm × 10 mm × 0.4 mm was taken, polished, washed with acetone and dried, and then the surface of the CVD diamond sheet was subjected to structured laser irradiation treatment using a nanosecond laser in an air atmosphere. Considering the heat dissipation of the diamond substrate during the laser irradiation treatment, the angle between the laser incident direction of the laser and the surface to be processed of the diamond substrate was 80°. After laser irradiation, a number of independent graphite modules were formed on the diamond surface. The graphite modules were parallel to each other and equidistantly distributed. The distance between two adjacent graphite modules was 0.8 mm, and the width of the graphite module was 1 mm.

[0044] When laser irradiation treatment is performed, laser filling scanning is performed in different areas starting from the edge of the CVD diamond sheet to form a microstructure with periodic papillae. The size of each area is 10mm×1mm, and the spacing between each area is 0.8mm. The laser operation parameters include: pulse frequency of 30kHz, spot diameter of 20μm, laser power of 8W, and scanning spacing of 1μm.

[0045] Step 2: Mechanical cleavage treatment:

[0046] The outer layer of the graphite module prepared in step 1 is mechanically cleaved by a flywheel, wherein the flywheel is a stainless steel flywheel with a brushed and polished surface, and the outer surface of the stainless steel flywheel is flat, the outer diameter of the stainless steel flywheel is 120 mm, and the thickness is 8 mm. The operating conditions of the mechanical cleavage include: the flywheel feed control accuracy is 1 μm, and the flywheel speed is 2000 r / min. After the mechanical cleavage is completed, the outer layer of each graphite module is cleaved into a graphene layer formed by a plurality of graphene sheets, and the angle between the graphene sheet and the surface of the diamond substrate in the graphene layer is 30 to 40°.

[0047] Step 3: Electrochemical stripping treatment:

[0048] The graphene layer is electrochemically stripped so that the angle between the graphene sheets in the graphene layer and the surface of the diamond substrate is 80-90 degrees, forming a micro-nano-scale nearly vertical graphene layer with a thickness of 12 μm.

[0049] The electrochemical stripping operation is as follows: the graphene product with an angle of 30-40° with the surface of the diamond substrate is used as the working anode, and the platinum sheet is used as the working cathode. The positive and negative electrodes are placed in parallel with a spacing of 3 cm. The electrochemical stripping is performed, and the applied voltage during stripping is 10V and the stripping time is 30 minutes. The size of the platinum sheet is 10×15×0.1mm 3 , purity>99.9%. In the electrochemical stripping operation, the electrolyte is a mixed aqueous solution of (NH4)2SO4 and NaOH, and the pH of the electrolyte is 9.

[0050] Step 4: Hydrophobic treatment:

[0051] The nearly vertical graphene layer at the micro-nano scale was immersed in a fluorinated liquid for 20 minutes to obtain an anti-icing graphene component with electrothermal properties.

[0052] Step 5: Circuit connection:

[0053] One end of several graphite modules is bonded to the first copper foil sheet through conductive silver paste, and the other end of several graphite modules is bonded to the second copper foil sheet through conductive silver paste. The first copper foil sheet and the second copper foil sheet are connected to the positive electrode and the negative electrode of the power supply respectively to form a parallel electric heating circuit. The distance between the first copper foil sheet and the second copper foil sheet is 10 mm.

[0054] Example 2

[0055] An anti-icing graphene article with electrothermal performance is prepared according to the method of Example 1, except that:

[0056] (1) The interval between each area during structured laser irradiation is 0.9 mm;

[0057] (2) Immerse the superhydrophobic graphene product in a fluoride solution for 18 minutes.

[0058] Example 3

[0059] An anti-icing graphene article with electrothermal performance is prepared according to the method of Example 1, except that:

[0060] (1) The interval between each area during structured laser irradiation is 1 mm;

[0061] (2) Immerse the superhydrophobic graphene product in a fluoride solution for 16 minutes.

[0062] Characterization and performance testing:

[0063] Figure 1 This is a schematic diagram of an anti-icing graphene component with electrothermal performance prepared in Example 1, in which each vertical graphene module is connected in parallel.

[0064] Figure 2 This is a surface SEM image of the vertical graphene module in the anti-icing graphene component with electrothermal properties prepared in Example 1.

[0065] Figure 3 a is an electron microscope image of the graphene layer after mechanical cleavage treatment in step 2 of Example 1, Figure 3 b is an electron microscope image of the graphene layer after electrochemical stripping in step 3 of Example 1.

[0066] Figure 4 This is a schematic diagram of the water contact angle of the anti-icing graphene product with electrothermal performance prepared in Example 1. Figure 4 It can be seen that the surface water contact angle of the graphene component is 129°, and the surface is a hydrophobic microstructure with periodic papillae.

[0067] The two ends of the graphene product prepared in Example 1 were bonded with copper foil electrodes using conductive silver paste, and the same heat flux density was applied to both ends. The heating rate and the highest steady-state temperature of Example 1 and the metal wire electric heating film were tested and compared. The test results are shown in Figure 5 and Tables 1 to 2, by Figure 5 As shown in Tables 1 and 2, compared with the metal wire electric heating film, the electric heating graphene product prepared by the present invention has higher electric heating conversion efficiency and stronger electric heating performance.

[0068] Table 1-Electrical performance parameters of CDGG electric heating components at room temperature

[0069]

[0070] Table 2 - Electric heating performance parameters of traditional metal wire electric heating components at room temperature

[0071]

[0072] The above are only preferred implementations of the present invention. The protection scope of the present invention is not limited to the above embodiments. All technical solutions under the concept of the present invention belong to the protection scope of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications without departing from the principle of the present invention should be regarded as the protection scope of the present invention.

Claims

1. A method for preparing an anti-icing graphene product with electrothermal performance, characterized in that: The following steps are involved: The surface of the diamond substrate is subjected to laser irradiation treatment to form a plurality of mutually independent graphite modules on the surface of the diamond substrate; The outer layer of the graphite module is subjected to mechanical cleavage treatment, so that the outer layer of each graphite module is cleaved into a graphene layer formed by a plurality of graphene sheets, and the angle between the graphene sheets and the surface of the diamond substrate in the graphene layer is 30-40°; Electrochemically exfoliating the graphene layer so that the angle between the graphene sheets in the graphene layer and the surface of the diamond substrate is 80-90°, forming a nearly vertical graphene layer at a micro-nano scale; The surface of the micro-nano-scale nearly vertical graphene layer is subjected to a hydrophobic treatment to obtain an anti-icing graphene product with electrothermal performance.

2. The method for preparing an anti-icing graphene product with electrothermal performance according to claim 1, characterized in that: The diamond substrate is a diamond-coated component, comprising a substrate and a diamond coating. The diamond coating is prepared on the substrate by a chemical vapor deposition method, and the thickness of the diamond coating is not greater than 20 μm.

3. The method for preparing an anti-icing graphene product with electrothermal performance according to claim 1, characterized in that: The plurality of graphite modules are parallel to each other, one end of the plurality of graphite modules is bonded to the first copper foil metal sheet through conductive silver paste, and the other end of the plurality of graphite modules is bonded to the second copper foil metal sheet through conductive silver paste.

4. The method for preparing an anti-icing graphene product with electrothermal performance according to claim 1, characterized in that: Among the plurality of graphite modules, the distance between two adjacent graphite modules is 0.8-1 mm, and the width of the graphite module is 1 mm; the thickness of the micro-nano scale nearly vertical graphene layer is not greater than 12 μm.

5. The method for preparing an anti-icing graphene product with electrothermal performance according to claim 1, characterized in that: The hydrophobic treatment is specifically as follows: immersing the micro-nano scale nearly vertical graphene layer in a fluorinated liquid for 18 to 20 minutes to obtain an anti-icing graphene product.

6. The method for preparing an anti-icing graphene product with electrothermal performance according to claim 1, characterized in that: The equipment used for the laser irradiation treatment is a nanosecond laser; In the laser irradiation operation, the pulse frequency is 30 kHz, the spot diameter is 20 μm, the laser power is 8 W, the scanning interval is 1 μm; and the angle between the incident direction of the nanosecond laser and the surface of the diamond substrate is 80°.

7. The method for preparing an anti-icing graphene product with electrothermal performance according to claim 1, characterized in that: The equipment used for the mechanical cleavage includes a flywheel, the outer diameter of the flywheel is 120 mm and the thickness is 8 mm; During the mechanical cleavage process, the flywheel feed control accuracy is 1 μm and the flywheel speed is 2000 r / min.

8. The method for preparing the anti-icing graphene product with electrothermal performance according to claim 1, characterized in that: The electrochemical stripping operation is specifically as follows: The graphene product with an angle of 30 to 40° with the surface of the diamond substrate was used as the working anode, and the platinum sheet was used as the working cathode for electrochemical stripping. The applied voltage during stripping was 10 V and the stripping time was 30 minutes.

9. The method for preparing the anti-icing graphene product with electrothermal performance according to claim 8, characterized in that: In the electrochemical stripping operation, the electrolyte is a mixed aqueous solution of (NH4)2SO4 and NaOH, and the pH of the electrolyte is 9; The platinum sheet has a size of 10×15×0.1 mm 3 , purity>99.9%; the positive and negative poles are placed in parallel with a distance of 3cm.

10. An anti-icing graphene product with electrothermal performance, prepared by the method according to any one of claims 1 to 9, characterized in that: The graphene product comprises a diamond substrate, a plurality of mutually parallel graphite modules, a graphene layer and a hydrophobic layer; the angle between the graphene sheet of the graphene layer and the surface of the diamond substrate is 80-90°; The diamond matrix, graphite module and graphene layer are connected in sequence through carbon-carbon covalent bonds.

Citation Information

Patent Citations

  • Method for in-situ generation of anti-attrition graphene film on surface of diamond and workpiece

    CN112479203A

  • Anti-icing and deicing graphene transparent heating film and preparation method thereof

    CN112867182A

  • Diamond workpiece with mixed-dimension carbon covalent laminated structure surface layer and preparation method thereof

    CN114735693A

  • Preparation method of upright graphene compound based on nano diamond-like carbon film

    CN114941128A

  • Method of manufacturing and modularizing assembled thermal management material based on diamond-graphene hybrid structure

    US20210238737A1